PEMBINAAN KARIER PNS JABATAN ESSELON II DAN III - Erdiansyah '; Zaili Rusli (Universitas Riau, 2013)
The purpose of this study is toanalyze what factors are inhibiting coaching career civil service positions Esselon II and III in theDistrict Secretariat Singingi Kuantan. This research was conducted at the District SecretariatSingingi Kuantan, where the population and the sample is Regent, Vice Regent, Assistant RegionalBaperjakat and BKD. Data was collected through questionnaire dissemination techniques, interviewsand observations, as the data collected were analyzed using descriptive analysis that prioritizesquantitative techniques. Results showed coaching career civil servant positions Esselon II and IIIin the District Secretariat Singingi Kuantan is good. While the factors that inhibit the developmentof civil service positions Esselon II and III in the District Secretariat Singingi Kuantan is thecapability of management and budget development.